2020
DOI: 10.15376/biores.15.3.5940-5950
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and fire properties of medium-density fiberboard prepared with huntite/hydromagnesite and zinc borate

Abstract: Effects of mineral-based fire retardants were investigated relative to the thermal and fire properties of medium-density fiberboard (MDF) via thermogravimetric analysis (TGA), limiting oxygen index (LOI), and thermal conductivity testing. Mineral-based chemicals containing huntite /hydromagnesite and zinc borate (ZB) were used at different concentrations. Changes in all values were observed depending on the type and concentration of chemicals. According to TGA evaluation, the residual weights in the MDF sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Results determined that the chemical compounds improved the water absorption and thickness swelling values and increased the fire resistance of the boards; however, they reduced the internal bond strength 48% (Martinka et al 2021). Ustaomer and Başer (2020) investigated the combustion and thermal properties of MDF boards produced using mineral-based chemicals containing huntite/hydromagnesite and zinc borate (ZB) at different concentrations. According to the results, all mineral-based chemicals significantly affected the limiting oxygen index (LOI) and thermogravimetric analysis values.…”
Section: Introductionmentioning
confidence: 99%
“…Results determined that the chemical compounds improved the water absorption and thickness swelling values and increased the fire resistance of the boards; however, they reduced the internal bond strength 48% (Martinka et al 2021). Ustaomer and Başer (2020) investigated the combustion and thermal properties of MDF boards produced using mineral-based chemicals containing huntite/hydromagnesite and zinc borate (ZB) at different concentrations. According to the results, all mineral-based chemicals significantly affected the limiting oxygen index (LOI) and thermogravimetric analysis values.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these measurements, it was determined that they are within the range of their standard values [13], [43], [44], [45] [46], [47], [48] , [49], [50] & [51]. The validation results confirmed that the experimental method has been verified and can be applied to measure the thermal conductivity and the extracted thermal resistance.…”
Section: Validation Of the Measuring Methodsmentioning
confidence: 77%
“…In contrast to ATH (1300 Jg -1 ), HH has a lower enthalpy of decomposition (990 Jg -1 ) [15][16][17]. Thus, the flame retardancy action of HH is enhanced with synergic action studies employing red phosphorus [18], expandable graphite [19], zinc borate [20,21], antimony trioxide (Sb 2 O 3 ) [22][23][24], and boric acid [22].…”
Section: Introductionmentioning
confidence: 99%